Reading preferences and their effects towards BEN 7 academic performance / Nur Fatin Nabila Abd Rahman - Abd Rahman, Nur Fatin Nabila (Akademi Pengajian Bahasa, 2019)
This study aimed to identify BEN 7 students' reading preferences that might affect their academic performance. From observation and experience in teaching, reading materials may have impacted students' comprehension and interest, and subsequently their academic performance. In this study, the respondents were 60 final year Bachelor of English with Communication (BEN) students from Faculty of Languages and Communication in UniSZA. The respodents were selected via purposive sampling, and the questionnaires designed were disseminated to them. The software, Statistical Package for Social Sciences (SPSS) was used for data analysis and data was presented in the forms of frequency, percentage, mean, median, mode and standard deviation. As this study aimed to identify the reading preferences of BEN 7 students and the effectiveness of the chosen reading materials for their academic performance, this research can probably help to recommend the learners and educators the suitable reading materials based on learning contexts.